Healthy food is nutritious, but organic food is healthy because it is pure: The negotiation of healthy food choices by Danish consumers of organic food. (January 2019) - Ditlevsen, Kia; Sandøe, Peter; Lassen, Jesper
Highlights: Qualitative investigation of how consumers of organic food products define health. Three overall concepts of health were found in existing research literature. Health is an important motivation for buying organic food products. Consumers relate the healthiness of organic food to purity. Healthiness in general is, by contrast, primarily understood as nutritional value. Abstract: There is increasing demand for organic food products throughout the Western world. Health concerns have frequently been found to be the main motivation of consumers purchasing organic products, but the literature on consumer preferences and behavior is less clear about what 'health' means to consumers of these products, and because of this it remains unclear what exactly drives consumers to choose organic products. This article investigates health from the perspective of consumers, and analyzes negotiations of, and justifications behind, their consumption preferences. The analysis is based on a focus group study conducted in Denmark in 2016. Three different understandings of health can be found when consumers explain their preferences for organic products: Health as purity; Health as pleasure, and a Holistic perspective on health. The first two are familiar from the literature on food. The third, which reflects principles behind organic agriculture, is less documented in the context of consumption. Health as purity was the dominant understanding of health used by the participants when explaining why they purchased organic food products. When participants discussed healthy eating in general, detached from a specific context, most employed a purely nutritional perspective as a definitive argument in supporting claims about healthy eating. The paper's findings have implications for future research on organic consumption. They also have practical implications for organic food producers and manufacturers.